2007
DOI: 10.1243/09576509jpe314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of volute geometry on the steady and unsteady performance of mixed-flow turbines

Abstract: The steady and unsteady performance of two mixed-flow turbocharger turbine rotors has been investigated. These rotors differ mainly in their inlet blade angle geometry; one has a constant blade angle (rotor A) and the other a notionally constant incidence angle (rotor B). The results indicate that the constant blade inlet angle design offers improved efficiency characteristics over the constant incidence one with total-to-static efficiency at the design point ranging between 0.7 and 0.76. A detailed assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…The efficiency shows hysteresis-like behaviour that has also reported in other studies for mixed flow turbines [5,16]. The area covered by the pulse period is larger at plane E than at the trailing edge.…”
Section: Time-accurate Performance With Pulsatile Inlet Flowsupporting
confidence: 84%
See 2 more Smart Citations
“…The efficiency shows hysteresis-like behaviour that has also reported in other studies for mixed flow turbines [5,16]. The area covered by the pulse period is larger at plane E than at the trailing edge.…”
Section: Time-accurate Performance With Pulsatile Inlet Flowsupporting
confidence: 84%
“…Hysteresis-like behaviour is seen during the pulse period. Similar kind of behaviour has also been found in papers studying mixed flow turbines [5,16]. The behaviour in the studied case is relatively symmetrical compared to the studies in the literature.…”
Section: Time-accurate Performance With Pulsatile Inlet Flowsupporting
confidence: 84%
See 1 more Smart Citation
“…There are limited documented investigations on the effects of volute cross-sectional shape on a turbine performance under pulsating flow conditions. One such research was by Hakeem et al [19], where a volute with approximately trapezoidal cross-sectional shape was modified into an approximately elliptic shape. This was achieved by rounding the corners and consequently tested with a mixed-flow turbine rotor.…”
Section: Introductionmentioning
confidence: 99%
“…The general opinion is that the impeller can be treated as quasi-stationary, whereas almost all the accumulation and wave effects are located in the volute [9,10]. Hakeem et al [11] tested the influence of the volute geometry in turbine performance under steady and unsteady conditions, showing differences in the observed behaviour between steady-state and unsteady tests. Although done for a radial compressor, Abdelmadjid et al [12] showed big effects in compressor performance due to variations in its volute geometry using CFD simulations.…”
Section: Introductionmentioning
confidence: 99%